2020
DOI: 10.1371/journal.pone.0233368
|View full text |Cite
|
Sign up to set email alerts
|

Low coverage of HIV testing among adolescents and young adults in Nigeria: Implication for achieving the UNAIDS first 95

Abstract: Background Most studies on HIV testing among young people in Nigeria are not nationally representative. As such, recent nationally representative data, such as the Multiple Indicator Cluster Survey (MICS), could help assess the current level of HIV testing among young people, a key target population for HIV prevention in the country. In this study, we examined the coverage and factors associated with HIV testing among adolescents and young adults (AYA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
72
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 30 publications
29
72
9
Order By: Relevance
“…Of the other determinants analysed, this study found strong evidence of higher odds of HIV testing among the most educated women, consistent with other studies on youth in the SSA region (19,32,60). The education-based inequity widened in the last survey, mostly among non-pregnant women, indicating the need to reach the least educated youths.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the other determinants analysed, this study found strong evidence of higher odds of HIV testing among the most educated women, consistent with other studies on youth in the SSA region (19,32,60). The education-based inequity widened in the last survey, mostly among non-pregnant women, indicating the need to reach the least educated youths.…”
Section: Discussionsupporting
confidence: 90%
“…The positive changes in testing uptake highlighted above among men and non-pregnant women have also been accompanied by a constant gap in the trend of HIV testing coverage between genders, with men being generally less well covered than women. Similar differences among youth were reported in Nigeria, Mozambique, and Uganda (60,61). The persistence of higher testing rates among non-pregnant women compared to men may be due to their higher demand of HTC services, caused by a greater perception of HIV risk resulting from their vulnerability and frequent exposures to sexual intercourse with older partners with whom they may have less control over condom use (8,62).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although testing for HIV is the cornerstone of ultimate prevention, most children and young adolescents are still unaware of their status [ 27 ]. Testing uptake is higher among adults compared to children as evidenced from the 2017 Multiple Indicators Cluster survey [ 28 ]. There is evidence that HIV negative women seroconvert during the breast feeding period [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that being female, being presently or previously married, having at least a primary education, living in an urban area, and coming from a wealthy home were linked to a higher likelihood of being screened for HIV. Although some of these factors have previously been linked to HIV screening [18,19], their geographical-level distributions and contributions have not been studied in Mozambique.…”
Section: Discussionmentioning
confidence: 99%